From Surveillant Assemblage to Surveillance Culture: Shifting Metaphors in Surveillance Studies - Hier, Sean P. (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
The surveillant assemblage enjoyed a good run in surveillance studies, where it served as a leading metaphor to guide 25 years of research. The time has come to find new metaphors to shape surveillance theorizing for the 21st century. This commentary considers surveillance culture as an alternative to the surveillant assemblage.